Progress on the Fifteenth General Review of Quotas-Report of the Executive Board to the Board of Governors (September 2018). (Policy Papers; Policy Paper ;, 2021)
Following the guidance on the Board of Governors Resolution No. 72-1 (December 2016), on September 21, 2018, the Executive Board discussed and adopted its third semi-annual report on progress on the Fifteenth Review. The report covered additional issues relating to both the adequacy of Fund resources and the quota formula and realigning quota shares, discussed in an informal meeting on July 30, 2018.